Modeling bole volume of Pinus durangensis in Guachochi, Chihuahua, México - Pompa-García, Marín; Hernández, Ciro; Prieto-Ruiz, José Ángel; Dávalos Sotelo, Raymundo (Instituto de Ecología, A.C., 2016)
Pinus durangensis is the most utilized and abundant tree species in the Guachochi region of the state of Chihuahua; however, there is a lack of appropriate knowledge to get accurate volume estimations. Therefore, the purpose of this study was to model the tapering of the bole to allow developing an equation to predict merchantable and total volume, which guarantees its operative application. For this purpose, a trigonometric model was fitted to 4 502 data pairs of 663 trees felled during harvesting operations. The goodness of fit test consisted of comparing the statistics, coefficient of determination, root mean square error, and a precision index. Model fitting includes the use of appropriate statistical procedures to account for the problems of autocorrelation and heterocedasticity associated with the development of taper equations. The model gave best results in terms of predictive capacity, and via mathematic integration, an equation for tapering was obtained which is compatible with the merchantable and the total volume. It was concluded that the generated equations have a solid statistical foundation, and therefore constitute an essential tool for improving accuracy in forestry inventories, assuring its usage not only in the study region but its application is recommended also in other sites, with the necessary adaptation of the model to the respective local conditions.